Herding behavior in the Chinese stock market and the impact of COVID-19 - Maquieira, Carlos; Espinosa-Méndez, Christian (Estudios de Economía, 2022)
We analyze herding behavior in the Chinese stock markets in the context of the COVID-19 pandemic using the cross-sectional absolute deviation (CSAD) model proposed by Chang et al. (2000) to detect herding behavior in the time period between January 30, 2001, and June 12, 2020. We consider stock prices for all firms listed (A-shares) on the Shanghai Stock Exchange (SHSE) and Shenzhen Stock Exchange (SZSE) in China. We report the presence of herding behavior during the period under study and that herding behavior becomes stronger after December 31, 2019 (the COVID-19 event date). We also study herding activity in the context of potential asymmetries in market return and volatility states. The results show that when the market return is high and the volatility is low, there is a more predominant herding behavior trend. Our results do not depend on using different time windows. Results do not change when time-varying coefficients are considered using rolling regressions. Other control variables which may be relevant in explaining CSAD do not change the results when included in the estimations.